+0  
 
0
452
1
avatar

-(-(-)(-)(-10x))=-5 solve for x

 

good luck lol

 Sep 25, 2017

Best Answer 

 #1
avatar+771 
+1

\(-(-(-)(-)(-10x))=-5\)

The first 2 negatives will become 1, since it is the same as -1 squared.

\((-)(-)(-10x)=-5\)

Same with the other two negative 1's.

\(-10x=-5\)

Divide both sides by -10.

\(x={-5\over -10}\)

Simplify.

\(x={1\over 2}\)

.
 Sep 26, 2017
 #1
avatar+771 
+1
Best Answer

\(-(-(-)(-)(-10x))=-5\)

The first 2 negatives will become 1, since it is the same as -1 squared.

\((-)(-)(-10x)=-5\)

Same with the other two negative 1's.

\(-10x=-5\)

Divide both sides by -10.

\(x={-5\over -10}\)

Simplify.

\(x={1\over 2}\)

AdamTaurus Sep 26, 2017

16 Online Users

avatar
avatar